Partisipasi Masyarakat dalam Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perkotaan di Desa Babalan Lor Kecamatan Bojong Kabupaten Pekalongan - Ivon Sagyta Ariastuti; Sulistyowati .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2017)
Program Nasional Pemberdayaan Masyarakat (PNPM) MandiriPerkotaan is one of the programs that comes as a solution to the problem ofpoverty. PNPM Mandiri Perkotaan is also present to overcome the problem ofpoverty in Pekalongan Regency, one of the assisted areas is in Babalan LorVillage Sub-Distric of Bojong Regency of Pekalongan. Furthermore, inimplementing a development program, it is necessary to involve all parties inother words, it requires participation of all components involved. Poverty andparticipation are two things that are closely related, the ineffectiveness ofparticipation and integration of the poor into the main institutions of society, isone of the characteristics of the culture of poverty. This research is conducted byusing qualitative research method. Data collection used in this research isinterview and documentation.The results show that the participation of the Babalan Lor villagecommunity can be concluded that it is running but needs to be improved. Villagersof Babalan Lor are only enthusiastic to be involved in the introduction andplanning process. While community involvement in the process of implementation,monitoring and evaluation even for the maintenance of the results of developmentneeds to be improved because people tend to be oriented towards the material orwages to be received, not the benefits of such development. On the other hand,there are encouraging factors of community participation that include: 1)Community Needs and 2) Village Facilitator Support, BKM Margo Mulyo andCommunity Leaders of Babalan Lor Village.Keywords: Participation, PNPM Mandiri Perkotaan